Comparison of evolutionary algorithms for estimation of parameters of the equivalent circuit of an AC motor (2018)
This work shows the comparison among three evolutionary algorithms used to estimate the parameters of the equivalent circuit of a three-phase induction motor. With the parameters of the motor is possible to calculate its efficiency. Applying statistical methods, the number of runs needed to obtain a confidence level of 95% is calculated. With this value each algorithm is used to estimate the motor's parameters and, according to the results, is possible to find the best